2012
DOI: 10.4028/www.scientific.net/amr.581-582.790
|View full text |Cite
|
Sign up to set email alerts
|

Study of Chelating Agents in Silicon Wafer Polishing Slurry

Abstract: Several chelating agents in silicon polishing slurries were studied about their effects on copper adhesion to the surface of silicon wafer. The copper contamination level on the Si wafer surface was measured with GFAAS. The results indicate that PAA and HEDP for acid slurries can reduce 80% copper contamination with respect to the situation of without chelating agent. EDTA, the most common chelating agent for alkaline slurries, has no predominant compared with FA/O and AEEA. The copper contamination on Si wafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Together with Na + and K + , Mg 2+ and Ca 2+ are main cations in several natural waters and biological fluids. ,, Moreover, they are also important in technological/industrial fields, because they are responsible for the hardness of waters and for scale formation and they strongly affect the performances of all products containing chelating agents (detergents, hair colorants, and so on). For all of these reasons, a comprehensive, systematic study of DTPMPA speciation in aqueous solutions could not neglect a study on the complexes formed by this ligand with both Mg 2+ and Ca 2+ . Therefore, some measurements were also performed in this work in NaCl­(aq) at T = 298.15 K and different ionic strengths (0 < I /mol L –1 ≤ 1.0) in the presence of Mg 2+ or Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with Na + and K + , Mg 2+ and Ca 2+ are main cations in several natural waters and biological fluids. ,, Moreover, they are also important in technological/industrial fields, because they are responsible for the hardness of waters and for scale formation and they strongly affect the performances of all products containing chelating agents (detergents, hair colorants, and so on). For all of these reasons, a comprehensive, systematic study of DTPMPA speciation in aqueous solutions could not neglect a study on the complexes formed by this ligand with both Mg 2+ and Ca 2+ . Therefore, some measurements were also performed in this work in NaCl­(aq) at T = 298.15 K and different ionic strengths (0 < I /mol L –1 ≤ 1.0) in the presence of Mg 2+ or Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…This is true mainly for several reasons, such as (i) a strong structural relationship to natural compounds, together with a high stability and low toxicity; (ii) the ease of attaching the phosphonate group to organic moieties (favoring the synthesis of many diverse ligands); and (iii) the coordinating ability of phosphonic derivatives toward several metal cations . Among the most common organophosphonates, diethylenetriamine- N , N , N ′, N ″, N ″-pentakis­(methylenephosphonic acid), DTPMPA (Chart ), is becoming a preferred chelant in many applications in which strong metal chelation is desired (see, e.g., refs ), owing to the frequent absence of precipitation of some of its complexes over a wide pH range.…”
Section: Introductionmentioning
confidence: 99%
“…These ligands coordinate with metal ions through their electron-donating atoms, resulting in the formation of highly stable cyclic chelates that resist dissociation [ 4 ]. In the realm of integrated circuits and microelectronics, chelating agents play a critical role and find widespread applications in various processes, including substrate polishing, cleaning, and even thin film layer etching [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyun Soo Roh [ 10 ] proposed a series of carboxylic acid chelating agents for precision polishing. Additionally, Liu Yuling introduced specialized chelating agent FA/O for microelectronics and conducted research on its applications and impacts in silicon wafer polishing [ 5 ], cleaning [ 11 ], copper interconnect layer polishing [ 12 ], as well as improving the electrochemical corrosion between cobalt and copper in copper interconnect layer polishing processes [ 13 ]. The aforementioned chelating agents share analogous functional ligands, such as carboxyl groups, phosphorous acid groups, hydroxyl groups, amino groups, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted by Xie et al showed that the slurry containing 20 mmol of ammonium citrate caused a 71.6% increase in the MRR compared to the control group. Compared to the above additives, new additives with amine groups have also become popular additives for silicon wafer CMP, due to the following advantages: (1) they can achieve a higher MRR (>500 nm/min) [19,20], (2) they do not introduce contamination with metal ions such as Na + , K + , etc., and (3) they can be used as chelating agents to remove metal ions [21,22]. Polyamines are a representative class of amine additives that can achieve large MRR improvements.…”
Section: Introductionmentioning
confidence: 99%